2011
DOI: 10.1093/eurjhf/hfr041
|View full text |Cite
|
Sign up to set email alerts
|

Preventing ventricular dysfunction in pacemaker patients without advanced heart failure: results from a multicentre international randomized trial (PREVENT‐HF)

Abstract: See page 599 for the editorial comment on this article (doi:10.1093/eurjhf/hfr058) AimsPrevious experimental and clinical studies have consistently suggested that right ventricular (RV) apical pacing has important adverse effects. Ventricular pacing (VP), however, is required, and cannot be reduced in many patients with atrioventricular (AV) block. The PREVENT-HF study was an international randomized trial that explored differences in left ventricular (LV) remodelling during RV apical vs. biventricular (BIV) p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
73
0
6

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(81 citation statements)
references
References 36 publications
2
73
0
6
Order By: Relevance
“…Comparison with other studies is diffi cult in this case because various evaluation approaches have been used. Nevertheless, slight to moderate improvements are usually stated, particularly in the Biv mode (25,29). Other evaluation end points -pacing parameters -acted according to expectations and in agreement with published results.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Comparison with other studies is diffi cult in this case because various evaluation approaches have been used. Nevertheless, slight to moderate improvements are usually stated, particularly in the Biv mode (25,29). Other evaluation end points -pacing parameters -acted according to expectations and in agreement with published results.…”
Section: Discussionsupporting
confidence: 84%
“…The authors further suggested that EF decreases rapidly in vulnerable patients and that these patients might benefi t even more from BiV pacing. (6) No signifi cant changes in EF were found in either of the observed groups in the PREVENT-HF trial (29). Decrease of EF in BiV patients was also found (30), which supports our conclusions that change of EF in relatively healthy patients is not a reliable end point for comparison of patients with various pacing modes.…”
Section: Discussionsupporting
confidence: 80%
“…These studies have tested "de novo" CRT implantation in patients with a conventional pacing indication, both with preserved left ventricular systolic function [67][68][69] and with moderate-severe left ventricular dysfunction [70][71][72]. The results suggest that CRT plays a preventive role with regard to HF mortality/hospitalizations only in patients with left ventricular dysfunction (LVEF <40%).…”
Section: Patient Selectionmentioning
confidence: 99%
“…Pequeños estudios aleatorizados han señalado que los pacientes con disfunción del VI moderada-grave podrían beneficiarse de la TRC en lugar de la estimulación apical del VD convencional (tabla 15) [123][124][125][126][127][128][129][130] . En general, los objetivos primarios de estos estudios se sustituyeron por objetivos hemodinámicos.…”
Section: Estimulación Cardiaca Con Terapia De Resincronización Cardiaunclassified